Pengaruh Makanan Halal dan Haram Terhadap Kondisi Spiritual Manusia Menurut Imam Al-Ghazali - Yanti, Fitri (UIN Sumatera Utara, 2023)
The Qur'an is a guide for mankind, all aspects are discussed in the Qur'an, one of which is related to halal and haram food. So, as Muslims, we must obey and submit to the teachings of the Islamic religion, so that humans will get blessings in their lives because they carry out what Allah has commanded. Halal food is food that is allowed in Islamic law to consume it, the appropriate food is taught in Islamic law, namely halalan thoyyiban (halal and good). On the other hand, haram food is food that is prohibited in Islam and is obtained from theft. Usually Allah forbids something there must be shortcomings and harms, both what we already know and what we don't know and everything that Allah has forbidden there must be wisdom behind it. Food and drink as well as a living earned in an unlawful way are also very influential in the life of a Muslim. Among them, it is stated that haram food is one of the reasons why it is difficult for one's prayer to be answered. Even in the hereafter, hell is more deserving of eating the body of someone who grew up from unclean food. On the other hand, halal food will have a positive influence on the life of a Muslim. Halal food will make it easier for someone to do good deeds. Halal food also acts as a deterrent and antidote to various diseases.and Improving the Condition of the brain and learning motivation of students.Keywords: Influence, Food, Halal, Haram.